Permeability variation and anisotropy of gas hydrate-bearing pressure-core sediments recovered from the Krishna–Godavari Basin, offshore India - Yoneda, Jun; Oshima, Motoi; Kida, Masato; Kato, Akira; Konno, Yoshihiro; Jin, Yusuke; Jang, Junbong; Waite, William F.; Kumar, Pushpendra; Tenma, Norio (Marine and petroleum geology, 2019)
Permeability measurements were conducted on gas hydrate-bearing pressure-core sediments recovered from the Krishna–Godavari Basin during India's National Gas Hydrate Program Expedition 02. Pressure cores collected in the deep seabed of the Indian Ocean were cut and stored under high pressure and low temperature on the D/V Chikyu using pressure core analyzing tools. A total of 25, 1.2-m storage chambers were transferred to Japan from India for pressure core studies using pressure-core analysis tools at the National Institute of Advanced Industrial Science and Technology. The sediment core's pressure and temperature were maintained within the hydrate stability conditions during the entire process of transfer and loading into a triaxial testing apparatus called TACTT to preserve the hydrate, which can simulate the in-situ effective stress state under triaxial conditions. The hydrate saturation of the samples was in the range of 50–90%. It was found that the initial effective water permeability was in range of 0.01 mD to tens of mD, depending on the hydrate saturation and the mean particle size of the host sediment. The hydrate pore space morphology is also a critical factor, and results suggest hydrates are forming in the pore centers of sand grains as pore filling, but also as a sediment grain coating. In a first for gas hydrate-bearing pressure cores, the permeability anisotropy was established via vertical and horizontal flow tests combined with a pore fluid flow simulation. The horizontal/vertical permeability ratio was found to be 4. Additionally, the effective stress dependency of permeability was investigated by performing flow tests at different effective stresses. Due to decreasing porosity and particle crushing, the permeability dropped by approximately 90% for an effective stress increase of 10 MPa. •The initial effective permeability of hydrate-bearing sediments was measured.•The horizontal/vertical permeability ratio of the hydrate-bearing sediment is 4.•Permeability becomes approximately 1/10 when effective stress increases by 10 MPa.